Volume 1: Large Bore Engines; Fuels; Advanced Combustion 2015
DOI: 10.1115/icef2015-1067
|View full text |Cite
|
Sign up to set email alerts
|

Emissions From a Diesel Engine Operating in a Dual-Fuel Mode Using Port-Fuel Injection of Heated Hydrous Ethanol

Abstract: Aftermarket dual-fuel injection systems in diesel engines using hydrous ethanol have been developed as a means to lower emissions from older diesel-powered equipment. However, our previous work has shown that the emissions benefits of currently available aftermarket intake fumigation injection systems can be inconsistent with manufacturer claims. Our current study evaluates a newly developed aftermarket dual fuel system that incorporates a novel fuel heating system and port fuel injection (PFI). This paper des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
2
1
1
Order By: Relevance
“…Overall, soot emissions decreased drastically, reaching near 90% reduction from CDC levels at high FEF. This result is somewhat contrary to our earlier hydrous ethanol PFI work [1][2][3] which showed that soot emissions remained high even at significant FEF. With reformed ethanol, as FEF increased, engine combustion was more premixed with significantly less directly injected diesel.…”
Section: Engine Performance and Emissionscontrasting
confidence: 99%
See 2 more Smart Citations
“…Overall, soot emissions decreased drastically, reaching near 90% reduction from CDC levels at high FEF. This result is somewhat contrary to our earlier hydrous ethanol PFI work [1][2][3] which showed that soot emissions remained high even at significant FEF. With reformed ethanol, as FEF increased, engine combustion was more premixed with significantly less directly injected diesel.…”
Section: Engine Performance and Emissionscontrasting
confidence: 99%
“…However, the high load condition experienced only a minor increase before decreasing, indicative of the high CE seen during this condition, providing further evidence that ISR operation is most beneficial at high loads. Unlike our previous work with hydrous ethanol [1][2][3], no unburned ethanol was present at engine outlet conditions. Instead, THC emissions consisted mainly of methane, depicted in Figure 6 and smaller amounts of acetaldehyde and formaldehyde.…”
Section: Engine Performance and Emissionsmentioning
confidence: 87%
See 1 more Smart Citation
“…Hwang, and W.F. Northrop [50], while e-diesel can reduce particulate emissions, there remains controversy over its effects on NOx, CO, and HC emissions. Additionally, the low flash point of e-diesel could pose safety challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Beim Übergang vom klassischen Dual-Fuel hin zum RCCI-Betrieb konnten ein weiterer Rückgang der Stickstoffoxid-Emissionen beobachtet und auch der Kohlenstoffmonoxid-sowie der Kohlenwasserstoffausstoß gesenkt werden. Nord et al[62] untersuchten die Saugrohreinbringung von vorgewärmtem, flüssigem Ethanol mit 10 % Wassergehalt. Durch die Vorwärmung wurde die maximal mögliche Substitutionsrate bei niedriger Last erhöht, jedoch bei höheren Lasten reduziert.…”
unclassified